QUALITY OF LIFE AND ITS ASSOCIATION WITH BONE TURNOVER MARKERS IN PATIENTS WITH THALASSEMIA - Ms, Fatimah Zaherah; Mf, Nazirah (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION As a result of improved treatment and longer life expectancy, thalassemia is now extending into adulthood. Although morbidity and mortality of patients have been reduced significantly, some aspects of the disease impact patients’ lives. This study investigated the quality of life of patients with transfusion dependent thalassemia and its association with bone turnover markers (BTM). METHODOLOGY This cross-sectional study recruited patients with transfusion-dependent thalassemia (n=40) from an adult haematology clinic. Patients younger than 18 years, with liver disease, on anti-resorptive therapy or corticosteroids were excluded. Participants underwent anthropometric measurements, pubertal assessment, biochemical profilesferritin, calcium, phosphate, 25-hydroxyvitamin D, bone turnover markers (s-CTX and s-P1NP), anterior pituitary hormone levels and glucagon stimulation testing. A self-administered 36-item Short Form (SF-36) health survey questionnaire was used to measure the patients’ quality of life (QOL) in the form of scores ranging from 0 (worst health) to 100 (best possible health). RESULTS A total of 40 patients were included. 47.5% were female and 52.5% were male, with mean age of 27.5 ± 5.2years and mean body mass index of 19.4 ± 2.45 kg/m2 . Hypovitaminosis D (<50 nmol/l), elevated serum ferritin (>500 ug/l) and endocrinopathies were found in 90% of patients while 27.5% had abnormal BTM, with significant negative correlation between vitamin D and bone formation marker, P1NP (r=-0.364, p=0.024). Majority of the patients had a physical and mental component summary score >50 (87.5% and 90% of patients respectively). Among the eight SF-36 domains, vitality showed the highest percentage of patients (40%) with score below 50, followed by general health and role physical (37.5% each). Bodily pain domain had significant correlation with P1NP (r=-0.311, p=0.05), whereas other components of patients’ physical or mental health were not affected by the abnormal bone turnover markers or hypovitaminosis D (p>0.05). CONCLUSION Bodily pain, a component of physical health and hypovitaminosis D had negative impact on bone-turnover. Overall, majority of participants had SF-36 health survey scores that trended towards good physical and mental health signaling satisfactory QOL despite being largely affected by comorbidities associated with transfusiondependent thalassemia.